Leadership: analysis of professional management performance in educational institutions in educational institutions - Quishpe-Mosquera, Kleber (2025)
This research work is based on the study of the leadership style of four educational institutions: fiscal, fiscal-commissioned, municipal and private, in which the auditing processes by the Ministry of Education (MINEDUC) showed ineffective results in terms of professional managerial performance. The objective of this study is to analyze the relationship between educational leadership and the achievement of educational quality standards of professional managerial performance. A mixed documentary and field approach was used. For the collection of information, surveys addressed to managers and teachers were used, validated by means of Cronbach's Alpha coefficient, and expert interviews were conducted. We worked with a probabilistic sample of 152 teachers from the referred institutions, 12 managers and 2 experts in professional managerial performance, officials of the Educational District 17D08-Los Chillos-Quito. It is highlighted that managerial leadership styles: transformational, distributed, dialogic and sustainable, present a very high significant relationship with the dimensions of managerial professional performance, in the opinion of the experts, managers should strengthen their management of the pedagogical leadership style. As the main conclusion, there is a high correlation between the distributed and sustainable leadership styles and the pedagogical management dimension, which allows identifying that it is necessary to strengthen managerial competencies in these two leadership styles due to their importance in meeting educational quality standards.